Family Caregiving in Aging Populations - Hill, T. author. aut Link
XIV, 132 p. 1 illus.
Keywords: Family members are increasingly likely to provide caregiving for older adults as the US population ages. This book summarizes what we know about caregiving by spouses and other intimate partners, adult children, siblings, grandchildren, friends, and other relatives, as well as by members of racial, ethnic, and sexual minority groups.